Nursing workload in a coronary unit according to the Nursing Activities Score - Rejane Reich; Débora Feijó Villas Bôas Vieira; Luciana Bjorklund de Lima; Eneida Rejane Rabelo-Silva
Objective: this study aimed to using the Nursing Activities Score to assess nursing workload in a coronary care unit, to assess the distribution of workload between shifts, and to compare the current staff of the care unit with that recommended by the instrument.Method: this was a longitudinal study, conducted in a teaching hospital in Southern Brazil, between April to June 2012.Results: A total of 604 NAS measures were obtained from the 61 patients included. The mean workload per shift was 47% (±12), with the greatest workload being reported in the afternoon shifts.Conclusion: according to the NAS, a mean of two and a maximum of 2.4 nursing professionals would be required per shift to meet all patient demands, suggesting that the current staff size in the CCU is adequate. The NAS was successful in assessing nursing workload and changes in patient demands over time.